Pemanfaatan Ruang Terbuka Hijau Yang Di Kelola Oleh Pemuda Di Desa Bulurejo - Mohamad Rijal Izzul Haq; Febriyanto Hermawan; Jason Marcelino Nugroho (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Green open space is a combination of several wide and wide spaces, green open space is also a place that is open in rural areas where there are plants, children's playgrounds, gajebo which have benefited people in rural areas directly or indirectly in a rural area. The green open space in the Bulurejo Village area has been managed by youths who form a community called My Lepen in utilizing the open land and then making it a green open space in fulfilling the interests of the people in Bulurejo Village. Green open space is a means of protecting plant ecosystems because nowadays green plants have been replaced by many residential buildings. it is very necessary to protect the ecosystem of green plants because green plants can make the environment beautiful and beautiful and for the convenience of the community.